2020
DOI: 10.1093/icvts/ivaa308
|View full text |Cite
|
Sign up to set email alerts
|

Perigraft reaction and incorporation of porcine and bovine pericardial patches

Abstract: OBJECTIVES Bovine and porcine pericardial patches are frequently used in cardiothoracic and vascular surgery. There are no guidelines recommending the usage of these patches for particular surgical approaches. However, these 2 materials supposedly possess different properties. The clinical advantage of porcine compared with bovine patches remains controversial. In this experimental study, we analysed the incorporation and vascularization of bovine and porcine pericardial patches during the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Bovine and porcine pericardial patches are frequently used in cardiothoracic and vascular surgery as prosthetic materials [ 16 , 59 , 60 , 61 , 62 ]. To avoid the detrimental effects of glutaraldehyde treatment, i.e., calcific degeneration [ 20 , 39 , 63 ] and cytotoxicity [ 56 , 64 ], tissue engineering has been focused on tissue decellularization with the purpose of creating a material that is easy to obtain, non-immunogenic, and that can be repopulated by the patient’s own cells in order to integrate and grow with the host.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine and porcine pericardial patches are frequently used in cardiothoracic and vascular surgery as prosthetic materials [ 16 , 59 , 60 , 61 , 62 ]. To avoid the detrimental effects of glutaraldehyde treatment, i.e., calcific degeneration [ 20 , 39 , 63 ] and cytotoxicity [ 56 , 64 ], tissue engineering has been focused on tissue decellularization with the purpose of creating a material that is easy to obtain, non-immunogenic, and that can be repopulated by the patient’s own cells in order to integrate and grow with the host.…”
Section: Discussionmentioning
confidence: 99%
“…A nine‐year experience comparing bovine patch angioplasty to direct suture, both commonly used in carotid endarterectomies, revealed much lower rates of restenosis and occlusion within the first year with bovine patch angioplasty (Biasi et al, 2002 ). Due to its xenogeneic nature, bovine patches may induce a moderate inflammatory host response, but cell proliferation and apoptosis immunohistochemical analysis have demonstrated that these parameters were not significantly affected at the implantation site (Schlachtenberger et al, 2021 ). However, given complexity of an irradiated wound bed, neovascularization may not occur, and thus further studies should assess thrombosis rates in microanastomosis of the vessel to bovine patch in free flap repairs.…”
Section: Discussionmentioning
confidence: 99%